Excavations at Portchester Castle Volume I: Roman - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1975)
This is an account of excavations at Portchester Castle which took place under Barry Cunliffe in 1961-72. The volume deals with Roman features and material recovered from these excavations. Included are descriptions of structures representing the shore fort and specialist reports on the material recovered, including pottery, coins, metalwork, human and animal bones, and archaeobotanical remains. A concluding chapter summarizes the results of the work in a historical and regional perspective.